‘‘Efficient and Secure Mobile Health SySstem using Cloud” (International Journal of Food and Nutritional Sciences, 2023)
Wireless wearable sensor devices and cloud of things aid patients in current health care. m Health offers more features than traditional health care services. It makes monitoring, sharing, diagnosing, and remotely engaging with patients via cloud of things easier. Wearable gadgets in health care raise various security concerns, including data privacy and security. Patient-driven mobile health has grown. Wearable sensors collect real-time patient data, which is aggregated and encrypted at end user devices. Doctors, nurses, and researchers store and access the encrypted data in the cloud. Sharing scalable encrypted data efficiently is difficult.This project proposes a Lightweight Sharable and Traceable (LiST) safe mobile health system. Patient data is encrypted end-to-end. LiST provides precise keyword search and protected data access control. Traitor tracing and user revocation are supported. Traitors sell their search key to coworkers and steal allowances. How-ever, the cloud handles most cryptographic computations while end user devices perform light tasks. LiST is secure without a random oracle. Extensive experimentation improves system performance. Health care information technology is growing worldwide. Only devolved countries used smart devices in health care. Today, poorer nations are also adopting it. Everyone wants to utilize smartphones and their apps. Users want mobile apps because of this transition. Even doctors and patients are comfortable using mobile devices for patient records and diagnosis.Information technology in healthcare is growing worldwide. In health care, mostly devolved countries used computers and technology. Now developing nations are too. Mobile networks in most of a country make everyone want to utilize them. Smart phone use has skyrocketed in recent years. Users want mobile apps because of this transition. Smartphones can now run most desktop apps.